Recents news from the Dodona Oracle. Apropos of a recent monograph by Éric Lhôte (Minerva, 2019)
The imminent appearance of the first volume of the Corpus of Oracular Lamellae of Dodona, with over 4.000 mostly unpublished fragments, has been announced. Meanwhile, Eric Lhôte has recently brought out a carefully crafted edition of previously published oracular texts from Dodona, together with a detailed study of the problems they entail. In this review-article we discuss some of Lhôte’s interpretations.
Keywords: Dodona; Greek oracles; Greek dialects